A Novel Model for Development, Organization, and Function of Gonadotropes in Fish Pituitary - Golan, Matan; Biran, Jakob; Levavi-Sivan, Berta (Frontiers in Endocrinology, 2014)
The gonadotropins follicle-stimulating hormone (FSH) and luteinizing hormone (LH) are key regulators of the reproductive axis in vertebrates. Despite the high popularity of zebrafish as a model organism for studying reproductive functions, to date no transgenic zebrafish with labeled gonadotropes have been introduced. Using gonadotropin regulatory elements from tilapia, we generated two transgenic zebrafish lines with labeled gonadotropes. The tilapia and zebrafish regulatory sequences were highly divergent but several conserved elements allowed the tilapia promoters to correctly drive the transgenes in zebrafish pituitaries. FSH cells reacted to stimulation with GnRH by proliferating and showing increased transgene fluorescence, whereas estrogen exposure caused a decrease in cell number and transgene fluorescence. Transgene fluorescence reflected the expression pattern of the endogenous fshb gene. Ontogenetic expression of the transgenes followed typical patterns, with FSH cells appearing early in development, and LH cells appearing later and increasing dramatically in number with the onset of puberty. Our transgenic lines provide a powerful tool for investigating the development, anatomy and function of the reproductive axis in lower vertebrates.